POSITIVE IMAGING IN PROTOCOLATE ACTIVITIES - Triana Hasmarini; Yanto Yanto; Asnawati Asnawati (SENGKUNI Journal (Social Science and Humanities Studies), 2020)
This study aims to find out positive imaging in the protocol activities of Bengkulu City Regional Secretariat. The research method used is descriptive qualitative data collection techniques based on observation, interviews, and documentation. Research informants were determined using purposive sampling method, namely three informants, a key informant and two main informants. In this study, positive imaging is analyzed based on the type of image according to Frank Jefkins, namely mirror image, current image, multiple image, corporate image and expected image (wish image) associated with protocol activities that have been carried out. The results showed that the protocol activities in the Regional Secretariat of Bengkulu City have a positive image, this can be seen from any protocol activities carried out always producing a positive impact or opinion from the leadership and the community. Positive imaging is done more to the expected image (wish image), meaning that the protocol activities are in accordance with what is expected by the leadership and the community. ABSTRACT This study aims to find out positive imaging in the protocol activities of Bengkulu City Regional Secretariat. The research method used is descriptive qualitative data collection techniques based on observation, interviews, and documentation. Research informants were determined using purposive sampling method, namely three informants, a key informant and two main informants. In this study, positive imaging is analyzed based on the type of image according to Frank Jefkins, namely mirror image, current image, multiple image, corporate image and expected image (wish image) associated with protocol activities that have been carried out. The results showed that the protocol activities in the Regional Secretariat of Bengkulu City have a positive image, this can be seen from any protocol activities carried out always producing a positive impact or opinion from the leadership and the community. Positive imaging is done more to the expected image (wish image), meaning that the protocol activities are in accordance with what is expected by the leadership and the community. .